The definitive guide to CentOS - Membrey, Peter; Verhoeven, Tim.; Angenendt, Ralph; Safari eBooks (Berkeley, Calif. : Apress, 2009)
"Author Peter Membrey provides the first definitive reference for CentOS, the workhorse Linux distribution that does the heavy lifting in small and medium-size enterprises without drawing too much attention to itself"--Resource description page.
Description based on print version record.
Includes index.
Keywords: Linux; Operating systems (Computers); Electronic books